Intussusception due to ectopic pancreatic tissue in a nine-month-old child - Salman, Bedii; Beşbaş, Nesrin; Coşkun, Turgay; Yılmazbayhan, Dilek; Sarıalioglu, Faik (The Turkish Journal of Pediatrics, 1992)
Ileo-colic intussusception was diagnosed in a nine-month-old male infant who presented with abdominal distention, irritability, and bilious vomiting. After reduction of the invaginated segment, a mass measuring one cm was palpated at the antimesenteric border of the terminal ileum. Pathological examination of the mass revealed ectopic pancreatic tissue, which most likely caused the intussusception.
Keywords: intussusception; ectopic pancreas